1988
DOI: 10.1161/01.cir.78.3.612
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of impaired regional myocardial perfusion by positron emission tomography with H2(15)O.

Abstract: Positron emission tomography with`50-labeled water (H2150) can be used to delineate abnormal regional myocardial blood flow in experimental animals. To determine the feasibility of this method in humans, we studied 33 subjects (9 normal volunteers and 24 patients with angiographically documented coronary artery disease) at rest and after myocardial hyperemia induced with intravenous infusion of dipyridamole. At rest, the myocardial region demonstrating the lowest relative H2`50 activity exhibited 71 + 8% of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The extent of myocardial infarction (MI) is related to patient outcomes (1 ), and clinicians often wish to have a sense for this critical measure. Imaging methods, although accurate, have limited accessibility and high cost.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of myocardial infarction (MI) is related to patient outcomes (1 ), and clinicians often wish to have a sense for this critical measure. Imaging methods, although accurate, have limited accessibility and high cost.…”
Section: To the Editormentioning
confidence: 99%
“…B-type natriuretic peptide (BNP) is a 32 amino acid cardiacsynthesized hormone that reduces blood pressure and increases sodium excretion (1 ). Following proteolytic cleavage of proBNP, a 108-amino acid precursor, an Nterminal fragment (NT-proBNP) and BNP are released (2 ).…”
Section: To the Editormentioning
confidence: 99%
“…Using blood flow indicators such as 13 NH 3 [82], 15 O-water [83], or 82 Rb [84] cardiac flow studies have been performed analogously to those done with SPECT ( Fig. 14) [85].…”
Section: Cardiological Petmentioning
confidence: 99%
“…Iida et al [15] showed diminished flow at rest in patients with coronary artery disease and Walsh ct al. [ 16] demonstrated that patients with significant coronary' ar tery disease could be identified. Araujo et al [10] quanti fied blood flow-in X patients with chronic stable angina and single vessel coronary artery' disease and showed that myocardial perfusion assessed after intravenous dipyrida mole was diminished in areas supplied by stenotic vessels compared w ith areas supplied by normal vessels where no discrepancies in myocardial perfusion were observed.…”
Section: Diagnosis O F Coronary Artery Disease and Effects O F Intervmentioning
confidence: 99%